CONTENT ON SPORTS PRODUCT INDUSTRY WEBSITES: DIGITAL MARKETING ANALYSIS - Ayu Angelina Pasaribu; Agus Ruhimat; Agus Dedi Subagja; Ilham Kamaruddin; Reza Saeful Rachman (LPPM STIE Muhammadiah Bandung, 2022)
The sports industry is an industry that has significant revenue potential. This can then be further optimized with proper marketing. Digital marketing through a website is a marketing step that has relatively good potential. This research will determine how digital marketing is carried out for sports products through websites. This research will be conducted using a qualitative approach. The data used in this study is secondary data derived from the results of previous research and studies. This study found that the website can function as a medium for spreading information related to sports products, especially products that have just come out. Then the help of SEO can increase the website’s optimization so that it will be on the first page of searches using Google so that, in the end, it will increase the amount of traffic on the website.